A metastable phase of tin in 3D integrated circuit solder microbumps. (June 2015) - Liu, Yingxia; Tamura, Nobumichi; Kim, Dong Wook; Gu, Sam; Tu, K.N.
Graphical abstract: Abstract : A metastable phase of Sn has been found to co-exist with β-Sn in Pb-free SnAg microbumps in 3D integrated circuit technology. Synchrotron microbeam X-ray diffraction, high-resolution TEM imaging and selected-area electron diffraction were used to confirm the metastable phase, which has an orthorhombic lattice, with lattice parameter a = 0.635 nm, b = 0.639 nm, and c = 1.147 nm. Its composition is Sn containing a few percent of Ni. A higher rate of nucleation might have enabled its formation.